'A Kind of Geological Novel': Wales and Travel Writing, 1783–1819. Issue 2 (July 2018) - Edwards, Elizabeth
Abstract : This article explores the layered and multivocal nature of Romantic-period travel writing in Wales through the theme of geology. Beginning with an analysis of the spectral sense of place that emerges from William Smith's 1815 geological map of England and Wales, it considers a range of travel texts, from the stones and fossils of Thomas Pennant's A Tour in Wales (1778–83), to Humphry Davy and Michael Faraday's early nineteenth-century Welsh travels, to little-known manuscript accounts. Wales is still the least-researched of the home nations in terms of the Enlightenment and the Romantic period, despite recent and ongoing work that has done much to increase its visibility. Travel writing, meanwhile, is a form whose popularity in the period is now little recognised. These points doubly position Welsh travel writing on the fringes of our field, in an outlying location compounded by the genre's status as a category that defies easy definition.